Increasing Fashion Design Creativity by Using the Ibis Paint X Application Module (Universitas Negeri Semarang, 2021)
The development of technology in the world of education is very helpful, especially in improving the quality of learning. This requires the world of education to adapt it. The characteristics of students in the 21st century as the digital generation make teachers have to be able to understand them. Thus, the teachers need to provide learning media that is adaptable to technological developments. Specifically, this research aims to: Develop a module on the subject of Fashion Design; investigate the feasibility of the module on the subject of Fashion Drawing; and find the increase of students’ creativity in Digital Fashion Design subject for Grade XI students by using the Ibis Paint X media. Research on Development of learning media in the form of this module uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The data analysis in this study consisted of: Determining the feasibility of the module; Determining the practicality of the module; and Determining the level of students’ creativity. The feasibility test of the module resulted a very feasible category and the practicality test of the module showed a very practical category. The module that was developed was also tested for its effectiveness, it had an N-Gain value of 78, which means that the module was effective and the result of the students’ creativity level was in the creative category. Based on the results of the study, it can be concluded that the module developed in this research is very feasible, very practical and creative to be used in Digital Fashion Design learning for vocational students of Fashion Design.